STAKEHOLDERS' INTERESTS IN POLICY IMPLEMENTATION: A CASE STUDY OF REGIONAL ASSET MANAGEMENT IN BANTEN PROVINCE - Komara, Syifa Rachmania (JANE - Jurnal Administrasi Negara, 2025)
Stakeholders' interests play a pivotal role in policy implementation, particularly in the management of regional assets. This study aims to analyze the interests affected during the implementation of regional asset management policies in Banten Province. Using a qualitative approach, the research explores the dynamics among involved actors, the prioritization of different interests, and their impacts on policy success. Data were collected through in-depth interviews, document analysis, and field observations. The findings reveal that conflicting interests among stakeholders—such as local governments, legislative bodies, and the public—significantly influence the effectiveness of policy implementation. This study provides strategic recommendations to enhance collaboration among actors to achieve more transparent and efficient regional asset management.